Arterial hypertension with comorbid chronic obstructive pulmonary disease: relationship between tolerance to physical exercise and structural and functional state of the heart. - T. Z. Burtniak; V. A. Potabasniy; V. I. Fesenko (Medičnì Perspektivi, 2019)
The aim of the study was to establish the relationship between tolerance to exercise, oxygen saturation, and structural and functional cardiac status in patients with hypertension in combination with COPD. This study included 120 patients with primary arterial hypertension of stage I-II, grade 1, 2, and 3 in combination with COPD of grades 2 and 3 and clinical groups A, B, C, D, consisting group 1; group 2 – 30 patients with primary hypertension, and group 3 – 30 patients with COPD; group 4 – 30 practically healthy people representative by age and sex. Research methods included general clinical examination (collection of complaints, anamnestic data) and instrumental research methods: electrocardiography (ECG), echocardiography, measurement of ambulatory blood pressure (BP) profile (ABPM), spirometry, pulsoxymetry (SpO2), 6-minutes walking test (6MWT). On examination of 120 patients with stage I-II, grade 1 hypertension was established in 19 (15.8%), grade 2 was in 83 (69.2%) and grade 3 was in 18 (15%) patients, respectively. COPD in clinical group A was diagnosed in 10 (8.3%), B – in 51 (42.5%), C – in 18 (15%) and D - in 41 (34.2%) patients, respectively. The most common was AH stage 2 with COPD in clinical group B – 35 (29.2%) cases and D – 31 (25.8%) cases. The 24-hour average systolic BP (SBP) in patients of the main group was 165 [144;178] mmHg, and the diastolic BP (DBP) was 103 [94;111] mmHg. The daytime average SBP was 160 [140;180] mmHg, and the DBP was 105 [93;117] mmHg accordingly. The night-time average SBP was 165 [155;175] mmHg, DBP – 100 [95;105] mmHg, heart rate (HR) – 83 [76;88] minutes, respiration rate (RR) – 21 [19;24] minutes. Decreases in index of chronotropic reserve (ICR) and the index of inotropic reserve (IIR) and load index indicate an increase in myocardial oxygen demand during exercise. There was an inverse correlation of IIR with SBP at rest (r= –0.42; p˂0.05) and a direct correlation with age (r=0.28; p˂0.05), which is significantly different from the control group. A direct correlation was found between the double product (DP) before and after exercise (r=0.43; p˂0.05), which indicated an increase in consumption of oxygen by the myocardium. We found a direct correlation between left atrium (LA) and the ratio of expiratory volume per 1 sec (FEV1) to the forced lung capacity (FEV) – FEV1/FVC (r=0.32; p˂0.05), which indicates the effect of the severity of bronchial obstruction on the level of left ventricular (LV) overload in patients with hypertension combined with COPD. The inverse correlation between thickness of the posterior wall of the LV (RVWT) and FEV1/FVC (r= -0.32; p˂0.05) indicates the contribution of disorders of bronchial patency and intrathoracic pressure with the level of BP to the development of concentric remodeling and LV hypertrophy. The inverse correlation between SV and COPD Assessment Test (CAT) (r= -0.32; p˂0.05) indicates an additional effect of COPD clinical severity on central hemodynamics in patients with hypertension. This relationship between the ventilatory and hemodynamic parameters is confirmed by the inverse correlation of  HR and  FVC  (r= –0.33; p˂0.05)),  left  ventricular  internal  dimension (LVEDD) of LV and  CAT (r= –0.24; p˂0.05)), stroke volume (SV) and Modified British Medical Research Questionnaire (mMRC) (r= –0.42; p.00.05), CAT and pack years (r=0.33; p˂0.05), inverse correlation between CAT and mMRC and FEV1, FVC and FEV1/FVC (r= -0.40;p˂0.05 and r= -0.45; p˂0.05), respectively. Linear regression analysis showed that changes in SV LV, LVEDD and SpO2 were dependent predictors of patient’s worsening state according to CAT (p˂0.05). The direct correlation was established between the desaturation (ΔSpO2) and ΔDP (r=0.48) and the inverse of ΔSBP (r= -0.29), 6MWT (r= -0.45), ICR (r= -0.34) and IIR (r= -0.29), which indicates a pronounced effect of hypoxemia on hemodynamics in patients with hypertension in combination with COPD. Comprehensive determination of cardiorespiratory reserve by 6-minute walk test, pulse oximetry and ambulatory blood pressure monitoring in patients with hypertension in combination with COPD makes it possible to establish disadaptation of the body to physical activity due to hypoxemia, decrease in the index of chrono- and inotropic reserves, which is an indication for administering appropriate therapy. In patients with hypertension combined with COPD, the degree of desaturation, stroke volume, end-diastolic parameters of the left ventricle, maximal size and volume of the left atrium, as well as remodeling of the left heart sections in the concentric direction can be considered as independent predictors of prognosis. The 6-minute walk test with desaturation can be used as an additional method of personalizing rehabilitation measures in patients with hypertension in combination with COPD.